The Impact of Legal Pluralism in the Dynamics of Human Rights Protection and its Implications for the Development of the National Legal System in Indonesia - Fenti Maya Sari; Syifa Nur Lathifah; I Putu Wahyu Budhi Sucita; Marsudi Dedi Putra (Rechtsvinding, 2026)
This research aims to analyze the impact of legal pluralism on the protection of human rights and examine its implications on the development of the national legal system in Indonesia in order to find a concept that bridges the diversity of the system with the principle of justice. The type of research used is normative law that focuses on the study of legal norms, principles, and doctrines through a statutory approach and a conceptual approach. Secondary legal materials collected through literature studies are analyzed qualitatively with a deductive thinking pattern to produce systematic and logical conclusions related to the problem being studied. Legal pluralism in Indonesia manifests in the interaction between state law, customary law, and religious law that apply simultaneously and provides a choice for people to choose norms that suit their interests. The existence of this diverse system has a positive impact on the recognition of indigenous peoples' rights and access to substantive justice, but on the other hand it triggers legal uncertainty and potential human rights violations due to the dominance of state law or the practice of forum shopping. The development of the national legal system responds to this reality through efforts to harmonize regulations, as seen in the constitutional recognition of the unity of customary law communities and the integration of living law in the new Criminal Code. Legal reform is directed at the establishment of a system that is no longer centralistic, but is able to accommodate local values in order to achieve a balance between national interests and the protection of the rights of minority groups.